EVIDENCE-BASED PSYCHOLOGICAL PRACTICE: A HISTORICAL PERSPECTIVE BASED ON PAST AND PRESENT - da Silva Junior, Hamilton Mendes; Torres, João Pedro Barboza; Oliveira, Higor Medeiros (Seven Editora, 2026)
Evidence-Based Psychological Practice (EBPP) represents a fundamental milestone in consolidating psychology as an applied science, integrating scientific evidence, clinical expertise, and patient preferences. This article presents a literature review on the historical evolution and current state of EBPP, covering 1999-2025. A systematic search was conducted in SciELO, PubMed, Google Scholar, ArXiv, Redalyc, PePSIC, and PsycNet databases. Thirty-two articles were selected and organized into five thematic categories: concepts and historical foundations, treatment efficacy, large-scale implementation, barriers and resistance, and Brazilian and Latin American context. Analysis revealed that EBPP evolved from a restricted list of empirically supported treatments to an integrative model valuing therapeutic relationship and cultural adaptation. Programs such as IAPT in England demonstrate feasibility of large-scale implementation. In Brazil, recent growth in scientific production is observed, but gaps persist in professional training and implementation barriers. EBPP constitutes an ethical and scientific imperative, demanding investments in training, research, and public policies in the Brazilian context.